Temporary Vascular Occlusion by Rapid Reverse Phase Polymer: A Preliminary In Vitro Study of Retrograde Injection - Einar Dregelid (International Journal of Biomaterials)
During vascular surgical operations, there is a need for a simpler and more reliable method of temporary arterial occlusion than those currently employed, especially of heavily calcified arteries. A thermosensitive polymer, LeGoo (LG) (Pluromed, Woburn, MA), has been used successfully for temporary vascular occlusion. It has hitherto been injected by a cannula that has been introduced into the artery to be occluded, here henceforth called the “cannulation method.” Injection into arterial ostia without cannulation, using an injection device that arrests blood flow during the injection, here henceforth called “a retrograde method” may enable temporary hemostasis when ostial stenoses render it impossible to inject LG using the cannulation method. The objective of the present study was to study the feasibility of a retrograde method and to compare it with the cannulation method in an in vitro model, incorporating a narrow orifice to simulate ostial stenosis, using tap water at 37°C instead of blood. The retrograde method of LG injection, using a modified paediatric Foley catheter, turned out to be feasible to produce a durable LG plug more reliably, at higher water pressure and with less deep LG injection than with the cannulation method.